Development of the system to integrate and generate content considering the cryptocurrent needs of users - Lytvyn, Vasyl; Vysotska, Victoria; Kuchkovskiy, Volodymyr; Bobyk, Іgor; Malanchuk, Oksana; Ryshkovets, Yuriy; Pelekh, Irina; Brodyak, Oksana; Bobrivetc, Vitaliy; Panasyuk, Valentyna (Eastern-European Journal of Enterprise Technologies, 2019)
We have investigated processes of analysis, integration, and content generation, taking into consideration the needs of the user in cryptocurrency. By using the developed formal model and the performed critical analysis of methods and technologies for predicting the exchange rate of cryptocurrency, we have built a general architecture of the content processing system that acquires data from different cryptocurrency Internet stock exchanges. General functional requirements to the intelligent cryptocurrency system that target the Internet users have been stated. We have investigated methods, models, and tools to improve the effective support for developing structural elements in the model of a decision support system that manages content according to the user’s needs. general architectures of the backend and frontend parts of an intelligent cryptocurrency system have been devised. We also developed software for the system of integration and generation of content considering the cryptocurrency needs of users. An analysis of results of experimental verification of the proposed method for content integration and generation taking into consideration the cryptocurrency needs of users has been performed. A special feature of the system is that it analyzes information from social media and builds a forecast of currency rates based on the acquired information. A given system makes it possible to guess the trend in an exchange rate fluctuation. Conferences of a particular cryptocurrency, new implementations, government decrees from different countries, affect a trend as well, so it too must be taken into consideration. In order to account for most cases, it is necessary to constantly accumulate information on the subject and to assign it to Tables in a database. A given process takes place using a specialized software bot that collects and indexes information. The system is characterized by the following features that favorably distinguish it from analogs: the speed of page generation; the presence of SSL certificate and TLS encryption; content of better quality as it is updated every minute; there are no inactive sections of the service; the mobile web-site layout does not copy content at subdomain; automated checks against e-mail spam messages on the exchange rate. The focus of the system is on the frequency of updates at the speed of data aggregation from the Internet stock exchanges and social networks.